CityApps: A bioinformatics tool for predicting the key residues of enzymes weakly interacting with monovalent metal ions. (May 2021) - Shi, Cheng; Liu, Song; Du, Guocheng
Graphical abstract: Highlights: The enrichment factor and dwell time were used to describe the interactions between enzyme and ions. Cityapps was developed to automate the calculation of the enrichment factor, dwell time, and RSMF. The residues critical for K + -mediated activation of a methyl parathion hydrolase were identified. Abstract: Monovalent metal ions play an essential role in some enzyme reactions. Due to the loose interactions, identifying the critical residues interacting with monovalent metal ions based on a molecular dynamic (MD) analysis is still a challenge. In this study, we first defined the enrichment factor (Eaa ) and the dwell time (td ) to describe the interactions with metal ions in each enzyme residue during MD analysis. A "sandwich-like" solvent box for MD analysis was then constructed to avoid the interference of the initial position of metal ions. Finally, a bioinformatics tool, CityApps, was developed to facilitate the automatization of MD analysis and the calculation of the interaction parameter. Using the tool, the key residues (D191, Q272, and N329) responsible for K + -mediated activation of a methyl parathion hydrolase (MPH) from Pseudomonas sp. WBC-3 were identified based on Eaa, td, and RMSF differences. Ala mutation showed that the mutant D191A/Q272A/N329A was difficult to be activated by 1 M K + . In addition, Q272A showed a 176.19 % increase in specific activity compared to the wild MPH type. Our results indicate that CityApps developed here could be an effective tool for identifying enzyme residues interacting with monovalent metal ions and those residues that are critical for catalytic reaction.